Identification of Poly(ADP-Ribose) Polymerase-1 as a Cell Cycle Regulator through Modulating Sp1 Mediated Transcription in Human Hepatoma Cells - Yang, Liu (Public Library of Science, 2013)
The transcription factor Sp1 is implicated in the activation of G0/G1 phase genes. Modulation of Sp1 transcription activities may affect G1-S checkpoint, resulting in changes in cell proliferation. In this study, our results demonstrated that activated poly(ADP-ribose) polymerase 1 (PARP-1) promoted cell proliferation by inhibiting Sp1 signaling pathway. Cell proliferation and cell cycle assays demonstrated that PARP inhibitors or PARP-1 siRNA treatment significantly inhibited proliferation of hepatoma cells and induced G0/G1 cell cycle arrest in hepatoma cells, while overexpression of PARP-1 or PARP-1 activator treatment promoted cell cycle progression. Simultaneously, inhibition of PARP-1 enhanced the expression of Sp1-mediated checkpoint proteins, such as p21 and p27. In this study, we also showed that Sp1 was poly(ADP-ribosyl)ated by PARP-1 in hepatoma cells. Poly(ADP-ribosyl)ation suppressed Sp1 mediated transcription through preventing Sp1 binding to the Sp1 response element present in the promoters of target genes. Taken together, these data indicated that PARP-1 inhibition attenuated the poly(ADP-ribosyl)ation of Sp1 and significantly increased the expression of Sp1 target genes, resulting in G0/G1 cell cycle arrest and the decreased proliferative ability of the hepatoma cells.